Influence of fluid volume variations on the calculated value of the left ventricular mass measured by echocardiogram in patients submitted to hemodialysis - Martin, Luis Cuadrado [UNESP]; Barretti, Pasqual [UNESP]; Cornejo, IV; Felipe, M. J.; Forti, A. H.; Matsubara, Beatriz Bojikian [UNESP]; Okoshi, Katashi [UNESP]; Padovani, Carlos Roberto [UNESP]; Teixeira-Caramori, J.; Tucci, PJF; Franco, RJD (Marcel Dekker Inc, 2003)
The left ventricular mass (LVM) measurement is of major importance for renal patients, as ventricular hypertrophy is an important prognostic index. The echo-cardiogram of the ventricular mass is larger before than it is after hemodialysis, which can confuse data interpretation. The aim of this work is to study the influence of alterations in fluid volume on the variations in measurements of ventricular mass observed during the course of a hemodialysis. Sixteen patients with chronic renal insufficiency in hemodialysis were evaluated at the Dialysis Unit of the University Hospital-UNESP, Botucatu, São Paulo State. The left ventricular mass was calculated from echocardiograms taken before and after hemodialysis and simultaneous ultra-filtration (12 patients: UF GROUP) and before and after hemodialysis isovolemic phase with sequential ultra-filtration (10 patients: ISO GROUP). Six of these patients were submitted to measurements of left ventricular mass before and after hemodialysis in both isovolemic and simultaneous ultra-filtration procedures. In the UF group, there was significant reduction in the following parameters before and after dialysis: diastolic diameter from 54.0 +/- 6.0 mm to 45.6 +/- 7.6 mm; left ventricular mass from 342 +/- 114 g to 265 +/- 117 g; and its respective index (IMVE) from 214 +/- 68 g/m(2) to 168 +/- 71 g/m(2). The ISO group showed no statistically significant variation. The behavior of the variables of six patients submitted to both observations confirm these results. In conclusion, the variations in echocardiogram measurements of the left ventricular mass relating to hemodialysis appear to be induced by alterations of the volemic condition.
Keywords: hemodialysis; left ventricular mass; M-mode echocardiogram; reliability